Pride Camp: Pilot study of an intervention to develop resilience and self-esteem among LGBTQ youth - Lance S. Weinhardt; Linda M. Wesp; Hui Xie; Jennifer (Jen); Jeanette Martín; Sarah DeGeorge; Caleb B. Weinhardt; Maren Hawkins; Patricia Stevens (BMC, 2021)
Abstract Background Many LGBTQ youth experience rejection and discrimination in their families and schools, and the range of interventions for improving their resilience and well-being is limited. We developed and piloted an LGBTQ-youth-focused intervention to build resilience and promote health equity, called Pride Camp, in an urban environment in the Midwest. Methods Using a mixed-method approach we examined the impact of Pride Camp on resilience and other measures of well-being among LGBTQ high school students who attended camp on a college campus in 2015, 2016, and 2017. Camp attendees and the research sample included a majority proportion of transgender and gender nonbinary (TGN) youth. Results Pre- and post-test data from our quantitative surveys (n = 28), indicated significant increases in resilience, self-esteem, and quality of life in LGBTQ youth who attended camp. Similar results were found among the TGN participants (n = 19). Qualitative data from focus groups indicated that specifically for TGN youth, the affirming environment at the camp provided social opportunities that they had not found elsewhere. Conclusions Findings suggest that the Pride Camp intervention provides a platform for LGBTQ youth to meet peers and engage in LGBTQ communities, improving their resilience and outlook on the future. A larger controlled study of the Pride Camp intervention including measurement of additional specific health outcomes over a longer follow-up period is warranted to examine the impact of this program on health equity.